Corrosion of Different Materials by Bio-Oil - Muhammad Ridhwan b Mod Razif, Muhammad Ridhwan (Universiti Teknologi Petronas, 2011)
Bio-oil is a new liquid fuel but very acidic. In this study, bio-oil pyrolyzed from empty fruit bunch (EFB) was prepared. Test was carried out to determine the corrosion different materials by the bio-oil. The test were conducted in three stages ( Experiment A, Experiment B and Experiment C) which involved different materials such as brass, iron, copper, aluminum, stainless steel 316 and 304, mild steel, polyvinyl chloride (PVC), polypropylene (PP), polyethylene teraphtalate (PET) and acrylic. Weight loss of the materials immersed in the bio-oil samples was recorded. The physical appearances of the materials were analyzed from photo taken. The results indicated that iron and mild steel were the least resistant to corrosion for metal while PVC was the least resistant to corrosion for plastic. Stainless steel (ss316 and ss304), PP and PET were not affected by the bio-oil. After corrosion, increased organic deposits were formed on iron, brass, copper, aluminum and mild steel but not on stainless steel, PVC, PP, PET and acrylic.